PERTUMBUHAN DAN HASIL JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA KOMPOSISI MEDIA TANAM SERBUK GERGAJI, AMPAS TEBU DAN JANTUNG PISANG YANG BERBEDA - Evy HanifahHanifah; Titik Suryani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract - Oyster mushroom is one of the edible mushrooms consumed by people because it contains high protein, vitamins, minerals, amino acids, low carbohydrates, fat and calories. The content of bagasse are carbons, hydrogens, oxygens, crude proteins, crude fibers, hemicelluloses, celluloses and lignins. The content of banana flowers are proteins, carbohydrates, fats, phosphorus, calcium, vitamin A, B1 and C. The purpose of this research was to determine the growth and yield of white oyster mushroom (Pleurotus ostreatus) on the different composition of sawdust, bagasse and banana flowers as the planting medium. This research is an experimental study using single factor completely randomized design consisting of five treatments: E0 (960 grams sawdust, without bagasse and banana flower), E1 (930 grams sawdust, 15 grams bagasse and 15 grams banana flowers), E2 (935 grams sawdust, 15 grams bagasse and 10 grams banana flowers), E3 (920 grams sawdust, 25 grams bagasse and 15 grams banana flowers) dan E4 (925 grams sawdust, 25 grams bagasse and 10 grams banana flowers), 3 replicates of each treatment. Data analysis used WAS One Way Anova test with a significance level of 0,05. The results showed that the best medium composition of 920 grams sawdust, 25 grams bagasse and 15 grams banana flowers (E3) significantly affected the growth of oyster mushroom mycelium (25,33 days), the number of oyster mushroom fruit bodies (23,33 fruits at harvest I and 9,00 fruits at harvest II) and the fresh weight of oyster mushroom fruit bodies (110,00 grams at harvest I and 83,33 grams at harvest II). Keywords : Pleurotus ostreatus, sawdust, bagasse, banana flowers